The slow book revolution creating a new culture of reading on college campuses and beyond - Lacy, Meagan (Libraries Unlimited, 2014)
"This inspiring guide shows how to implement the principles of the Slow Book movement in high schools, public libraries, and college campuses, with the ultimate goals of encouraging pensive reading habits and creating a lifelong enjoyment of books"..